2006
DOI: 10.1097/01.brs.0000194774.85971.df
|View full text |Cite
|
Sign up to set email alerts
|

Work Disability and Costs Caused by Recurrence of Low Back Pain: Longer and More Costly Than in First Episodes

Abstract: Recurrences contributed disproportionately to the total burden of work-related nonspecific LBI, through both additional care seeking and work disability. Results imply that those who have recurrences may be an especially important target for secondary prevention efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
76
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(88 citation statements)
references
References 41 publications
4
76
0
7
Order By: Relevance
“…Regarding WRLBP recurrence, it was recurrent for two-thirds of the P.Ts in the current study, the same result was reported by the American and Canadian P.Ts (11,14) , their general population had reported a recurrence of 33.9% nearly a half of the P.Ts population (24) . The high recurrence percentage can be attributed to the continuous exposure to the causative factor of workloads without effective change.…”
Section: Discussionsupporting
confidence: 77%
“…Regarding WRLBP recurrence, it was recurrent for two-thirds of the P.Ts in the current study, the same result was reported by the American and Canadian P.Ts (11,14) , their general population had reported a recurrence of 33.9% nearly a half of the P.Ts population (24) . The high recurrence percentage can be attributed to the continuous exposure to the causative factor of workloads without effective change.…”
Section: Discussionsupporting
confidence: 77%
“…This is not surprising since biomechanical studies have demonstrated how low backloads during common patient handling tasks frequently exceed recommended safe limits for maximal acceptable compressive forces on the back (10,11). The problem is further aggravated because, when first initiated, a history of back pain or injury is associated with recurrent back injury (12)(13)(14), which is often more severe and costly than the initial episode (12,14).…”
mentioning
confidence: 93%
“…For those working in occupations with high physical job demands, the prevalence of low back pain can exceed 60 percent (17). While some workers with back pain may recover with minimal interruption to employment, others experience prolonged periods of disability or recurring episodes (18) which have a negative impact on their employment status and financial stability (19). Since reintegrating workers with LBP is a common, and ongoing challenge faced by supervisors, and supervisors may accommodate different health conditions in unique ways, this study specifically explores how supervisors experience and make decisions about accommodating workers with LBP.…”
Section: Introductionmentioning
confidence: 99%